Optimisation of the WhatsApp Application in Learning Taḥsīn al-Qur'ān To Improve Students Reading al-Qur'ān Ability - Suwarno Suwarno; Ismet Nur; Rahmanita Zakaria; Evanirosa Evanirosa (Al-Ishlah: Jurnal Pendidikan, 2022)
Abstract